EVALUATION OF OPTIMAL TOP COAT THICKNESS IN COMPOSITE LTA/YSZ THERMAL BARRIER COATING BY COMPARATIVE STRESS DISTRIBUTION USING FINITE ELEMENT METHOD - Aziz, R.; Pasha, R.; Abbas, M. (The Nucleus, 2015)
Demand of high operating temperature in gas turbines for better efficiencies has forced researchers to explore novel materials with improved thermal properties. In this regard, LaTi2Al9O19 (LTA) is recently declared as a brilliant candidate for thermal barrier coatings (TBCs). Owing to potential advantages like high temperature stability & low thermal conductivity, researchers are striving to use it for modern gas turbines. An innovative concept of composite ceramic coating (LTA+YSZ) has been introduced to achieve improved set of thermal & mechanical properties. In this paper, a finite element analysis (FEA) has been employed to observe stress scattering with relatively varying thicknesses of compositional ceramic coats using commercially available software ANSYS. Optimum set of variables has been proposed based on the associative stress state data calculated from FEA results. Radial & axial stresses (Ïƒxx, Ïƒyy) are ascertained for composite system and ultimate values of stress are offered for comparison on quantitative grounds. Elastic strain energy stored in TGO is determined based on FE results to estimate the structural reliability of TBC. Conclusively, trend reveals that both radial & axial stresses are respectively proportional to increasing & decreasing thickness of YSZ. Comparing elastic strain energies, maximum life is evaluated in 1:4 for YSZ: LTA which shows that composite layer TBC system have improved stability than single layer system as reported in literature.